Modernising health care reinventing professions, the state and the public - Kuhlmann, Ellen 1957- (Policy Press, 2006)
Modernising health care: Reinventing professions, the state and the public is a crucial contribution to debates about the rapid modernisation of health care systems and the dynamics of changing modes of governance and citizenship
Title from publisher's bibliographic system (viewed on 19 Jan 2022)
Keywords: National health services / Great Britain; Public health / Great Britain; Medical care / Great Britain; Social service / Great Britain; Health planning / Great Britain